Understanding food insecurity in England: a systems-based approach - Charan Bijlani; Denise Ndlovu; Dianna Smith; Claire Thompson; Leandro Garcia; Cornelia Junghans; Eszter P. Vamos; Paraskevi Seferidi (Policy Design and Practice, 2025)
Food insecurity is a significant public health issue in England. National and local policies have not been able to adequately address its complex drivers, in part due to unintended consequences that arise from the way these policies interact with the system. Through an integrative review and group model building workshops with 17 subject matter experts, we developed four causal loop diagrams (CLDs) to map the interactions between food insecurity drivers and major policies such as Universal Credit, Healthy Start, and School Meal programs. The CLDs reveal that while these policies and interventions are intended to reduce food insecurity, specific implementation issues can unintentionally perpetuate food insecurity. These unintended consequences result in a shift in responsibility between governments and communities, with a subsequent erosion of public trust in governments and policies. This study highlights the need for redistributing responsibility back to governments, rebuilding trust and mitigating unintended consequences of current policies. By addressing the feedback mechanisms driving food insecurity, this research provides actionable insights and policy recommendations for creating equitable and effective policies.